Analisis Jaringan Distribusi Utama Di Kandis Pasar Minggu Menggunakan Epanet (Studi Kasus: Desa Sam-sam) - Panggabean, Hendrix SB; Siswanto, Siswanto; Trimaijon, Trimaijon (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Water is a very important need for human survival. In solving the piping problem in a region, a pipe network system model for the distribution of raw water which includes hydraulic equations for closed channels is required. In the study using EPANET program. Projection result from population of 2016-2035, Geometrik method become reference in determining clean water requirement, by using water requirement per person per 100 liter per second. Distribution of clean water needs using HDPE pipes. The pipe used has the smallest diameter of 90 mm and the diameter of 180mm diameter 1 and 200 to 110 mm in diameter 2 has a length of 31,007.64 meters, with junction or pipe connection 234, 1 IPA tank and 1 pump with liters per second.Keywords: EPANET, Water Pipe, Geometric Method.